Assessment of personality traits and skills of UPILS and non-ILS students as indicator of a career in information brokering - Moraña, Mark F.; Yang, Jackson V. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 2002)
Information brokering lies on the concept of information as commodity. An information broker searches for raw data that will solve a well-defined problem, packages the information into a usable form and delivers it to the client for a fee. An information broker is a reference librarian let loose. Thus, an information broker should possess the personality traits and skills of an entrepreneur and a librarian at the same time
This research was an assessment of skills and personality traits of UPILS and non-ILS students as indicators of a career in information brokering. A three-part questionnaire was used to facilitate the research with the first part dealing with awareness and knowledge of the concept of information brokering. The second part contained the skills and personality assessment and the third part was on the perception of students on information brokering in the Philippines and their willingness to engage in the profession. Fifteen (15) personality traits and ten (10) skills were identified for the assessment. Personality traits included, 1) Aggressiveness, 2) Curiosity, 3) Creativity and imagination. 4) Energy and Endurance,5) Enthusiasm, 6) Flexibility and adaptability, 7) Hard work, 8) Independence, 9) Initiative, 10) Optimism, 11) Patience and persistence, 12) Responsibility, 13) Risk-taking, 14) Self-confidence and 14) Sense of humor. Skills included, 1) Administrative ability, 2) Analytical skills, 3) Communication skills, 4) Interpersonal and empathy skills, 5)marketing ability, 6) Computer proficiency, 7)Information handling skills, 8) Reference skills, 9) Research skills, 10) Organization skills
The research found the sample of UPILS students more aware and knowledgeable of information brokering as a profession than the sample of non-ILS students. It also shows the sample UPILS students scoring higher on both personality and skills assessment than the samples of non-ILS students. The samples of UPILS students also are more willing to engage on information brokering than samples of non-ILS students. Information brokering as a profession is perceived to be applicable in the Philippine setting based on respondents' opinions
Vita
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: University of the Philippines Institute of Library and Information Science -- Students; Information services